BUSINESS MODEL CANVAS USAHA PRODUK MINUMAN SERBUK KEDELAI NEW MANDALA 525 (Studi Kasus di CV. Intan Alami, Kabupaten Garut) - Putri, Maura Zhafira; Rochdiani, Dini; Yudha, Eka Purna; Pardian, Pandi (Universitas Galuh, 2023)
Soybean is one of the food commodities as a source of vegetable protein which has good nutritional content. Soybean productivity has increased since 2019. In running its business, CV. Intan Alami requires an appropriate business strategy to be able to reintroduce the New Mandala 525 soybean powder beverage product. The purpose of this study is to describe the performance of the beverage product business and present the business model for the New Mandala 525 soybean powder beverage product. The research method used is a case study at CV. Natural Diamond, Garut Regency. The data analysis used is the business model canvas for the New Mandala 525 soy powder beverage product business. The results show the performance of the New Mandala 525 soybean powder beverage product business seen from approaches related to product, price, distribution/place/location, promotion, human resources (HR) and source of business capital, New Mandala 525 soybean powder drink is a powdered soybean beverage product made from 100% soybean seeds, sales are made directly and through distributors with promotional activities through electronic media. Human resources are obtained from the results of recruitment and collaboration with partners, business capital using private property and the results of cooperation agreements. The mapping of the nine elements of the business model canvas shows that the New Mandala 525 soybean powder beverage product is a superior product that has a value proposition to be able to compete in the market with a fairly broad customer segmentation. Having partners who can be relied upon to become supporters in reviving the New Mandala 525 soybean powder beverage business.